An Evaluation of Differentially Spliced Genes as Markers of Sex for Forensic Entomology, ,. Issue 5 (5th June 2020) - Jonika, Michelle M.; Hjelmen, Carl E.; Faris, Ashleigh M.; McGuane, Alexander S.; Tarone, Aaron M.
Abstract: Blow flies (Calliphoridae) are important medically and economically and are commonly used in forensics as temporal markers in death investigations. While phenotypic traits in adult flies can be sexually dimorphic, sex identification in immatures is difficult. Consequently, little is known about how sex may result in developmental disparities among sexes even though there are indications that they may be important in some instances. Since genetic mechanisms for sex are well studied in model flies and species of agricultural and medical importance, we exploit the sex‐specifically spliced genes transformer ( tra ) and doublesex ( dsx ) in the sex determination pathway to optimize a sex identification assay for immatures. Using known primer sets for tra and with a novel one for dsx, we develop PCR assays for identifying sex in four forensically relevant Calliphoridae species: Lucilia sericata (Meigen), Lucilia cuprina (Wiedemann), Cochliomyia macellaria (Fabricius), and Chrysomya rufifacies (Macquart) and evaluated their performance. Band detection rates were found to range from 71 to 100%, call rates ranged from 90 to 100%, and no error was found when bands could be called. Such information is informative for purposes of testimony and in preparation for development studies. The developed assays will assist in further differentiating sexually dimorphic differences in development of the Calliphoridae and aid in more accurately estimating insect age when age predictive markers (size, development time, molecular expression) are sexually dimorphic.